STRUKTUR DAN PENYEBARAN VEGETASI STRATA SAPLING DI KAWASAN HUTAN MANGROVE PULAU BENGKALIS PROVINSI RIAU - Yuslim Fauziah; Nursal '; Supriyanti ' (Program Studi Pendidikan Biologi, 2004)
The research about structure and distribution of sapling strata vegetation has been done at mangrove forest ecosystems in Bengkalis Islands Riau Province from March until November 2002. This study used quadrate methods with quadrate was placed along o f transect. Ten quadrate (10x5 m ) was make on the transects with systematically systems, Observation variable are Relative Density (KR), Relative frequency (FR), Relative Dominance (DR) and Informace Value. The results of data analysis showed that generally was founded 21 species frok, sapling stratum, That dominance species is Rhyzophora apiculata (132,79% ) at location VII (Desa Selat Baru), that what founded 2 sapling strata vegetation (Rhizophora apiculata dan Rhizophora mucronata) has been distributed all o f area study (100%), at mangrove forest of Bengkalis Islands Key words : Mangrove, structure, strata,, sapling, vegetation